2020
DOI: 10.1016/j.jclinepi.2020.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Inferential reproduction analysis demonstrated that “paracetamol for acute low back pain” trial conclusions were reproducible

Abstract: Objectives: The aim of this study was to reanalyze and reinterpret data obtained in Paracetamol in Acute Low Back Pain (PACE), the first large randomized controlled trial evaluating the efficacy of paracetamol in acute low back pain, to assess the inferential reproducibility of the original conclusions.Study Design and Setting: Mixed effects models were used to reanalyze pain intensity (primary outcome; 11-point Numeric Rating Scale) and physical functioning, health-related quality of life, sleep quality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…no difference between paracetamol vs placebo) were also found in the subgroups of patients with severe pain-intensity and severe impairment of physical functioning. Overall, the re-analysis confirmed the original analysis and results of the PACE-trial and strengthen its conclusions [40].…”
Section: Replication Of the Pace-trialsupporting
confidence: 76%
“…no difference between paracetamol vs placebo) were also found in the subgroups of patients with severe pain-intensity and severe impairment of physical functioning. Overall, the re-analysis confirmed the original analysis and results of the PACE-trial and strengthen its conclusions [40].…”
Section: Replication Of the Pace-trialsupporting
confidence: 76%
“…In the field of low back pain (LBP, the most disabling condition worldwide 13,24 ), conservative interventions are often administered to patients, 63 despite evidence suggesting that such interventions have modest effects(0-9 points on a scale of 0-100) at best when compared with placebo. 11,55,57 It has been suggested that sham oral medication could produce clinically meaningful change in pain scores in patients with LBP without a specific nociceptive source for their complaints (eg, LBP 24 ), 52 thus contradicting earlier evidence regarding the magnitude of placebo interventions for pain. 31 However, studies with a no intervention group were not included in this systematic review, which makes it impossible to actually estimate the magnitude of the placebo effect vs no intervention in LBP.…”
Section: Introductionmentioning
confidence: 99%
“…There are indeed positive examples for well-reproduced analyses and their added value in the current literature. In particular, in their re-analysis pursuing inferential reproducibility of the PACE ("paracetamol for acute low back pain") trial data, Schreijenberg et al were able to confirm the results from earlier analyses of the same data [10]. This re-analysis demonstrated that trial conclusions were reproducible even after replication with a different methodological approach.…”
Section: Introducing Reproducible Researchmentioning
confidence: 90%